Ineffective assistance of counsel as grounds for habeas corpus relief in post-conviction proceedings - Zielińska-Rapacz, Barbara (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The doctrine of habeas corpus is that no one should be imprisoned contrary to the law of the land. The habeas corpus review is used as a form of inquiry issued to test whether a conviction or restraint is lawful. However, before having a chance to present their case before a federal forum, state prisoners have to fulfill the state’s gatekeeping requirements, such as the exhaustion of all available state remedies, requirements of the Anti-Terrorism and Effective Death Penalty Act, and the absence of procedural default. Procedural default arises when the state court declines to address a prisoner’s federal claims because the prisoner failed to meet a state procedural requirement. To overcome the procedural default the petitioner has to satisfy the “cause-and-prejudice test.” In many cases the fulfillment of the “cause” element is often based on the claim of ineffective assistance of counsel. To prove the ineffective assistance of counsel, the petitioner has to satisfy the test consisting of two prongs: establishing the deficient performance of counsel and demonstrating that the deficient performance prejudiced the defense.In federal proceedings the rule is to raise the claim of the ineffective assistance of counsel in the collateral review. However, the right to a counsel does not extend to collateral attacks upon conviction, including a post-conviction appeal. Moreover, the counsel’s deficient performance does not constitute a basis for a procedural default reversal in the post-conviction claim. The abovementioned assertation may pose a question: what happens when the defendant is eligible to raise the ineffective assistance of counsel claim only in the collateral proceeding and the counsel representing the defendant in such a proceeding does not raise the claim?The Supreme Court resolved this matter in the decision from the Martinez v. Ryan case. The Court allowed for treating inefficient assistance of post-conviction counsel as a cause that could reverse procedural default. Taking into consideration the amount of ineffective assistance of counsel claims in habeas corpus review, the Martinez v. Ryan case may influence a fair amount of individuals seeking their constitutional rights and give them their last chance to contest unfair conviction.
Keywords: habeas corpus review; ineffective assistance of counsel; Martinez v. Ryan